The nature and essence of interpersonal relations between the subjects of pedagogical activity - Muskhadzhieva, T. A. (Vestnik Mininskogo universiteta, 2023)
Introduction. The study provides an analysis of modern theoretical research and approaches to the definition of the concept of "interpersonal relationships". The article reveals the nature of interpersonal relations, the relationship between the teacher and the student, their nature of mutual influence on each other. On the basis of theoretical analysis, ideas are formed about the system of interpersonal relations, its components, the specifics of building in the pedagogical process. The main attention is paid to interpersonal relations between the teacher and the student, which act as one of the main factors forming behavioral motives, communication skills, emotional culture of the individual and setting a vector in the development of cognitive interests of the student.methods of information transmission, the nature of interaction, which is the key to building a quality educational process. Materials and Methods. The article uses the following methods: analysis of normative documents; analysis of the current state of the problem in scientific literature and practice; study of pedagogical experience; generalization. Results. Theoretical studies and educational practice confirm that the non-constructive interaction of subjects of pedagogical activity contributes to the formation of low knowledge indicators in the student, lack of motivation to learn, the emergence of conflicts, difficulty in communication andhinder the full development of the child's personality. Constructive, humanistic relations between the teacher and the student are a key factor in the successful solution of pedagogical tasks. Interpersonal relations of the subjects of the pedagogical process are mutually influencing, are the starting point in creating a favorable psychological climate in the group, satisfaction with the work process and contribute to achieving a positive result of joint activities. Discussion and Conclusions. The conclusion reveals the role of the teacher as a leading figure building interpersonal relationships with the student, and these relationships occur in a complex system of interaction between student and teacher, students among themselves, family and school, teacher and teacher, who also influence educational and pedagogical interaction. The study of relations and interaction within the pedagogical dyad "teacher – student", the problems around which their main communications are formed, is based on the analysis of classical and modern scientific theories, the formulation of conceptual apparatus, the definition of forms of interaction, methods of information transmission, the nature of interaction, which is the key to building a quality educational process.